Autophagy impairment in human bile duct carcinoma cells - Petrungaro, Simonetta; de Franchis, Valerio; Filippini, Antonio; Facchiano, Antonio; Gaudio, Eugenio; Giampietri, Claudia (Frontiers in Physiology, 2023)
Bile duct epithelial cells, named cholangiocytes, may undergo a neoplastic transformation leading to cholangiocarcinoma. The role autophagy plays in cancer is still debated and few information are available in cholangiocarcinoma. We report in vitro data, at least in part validated in vivo,i ndicating that autophagy is impaired in intrahepatic cholangiocarcinoma cells, as compared to healthy cholangiocytes, evaluated through LC3II and p62 Western blot analyses. Autophagy impairment was found to be associated with low expression of TFEB protein and high expression of three proteins i.e. c-FLIP, caspase-10 and cleaved BCLAF-1, as compared to healthy cholangiocytes. We highlight biological effects of autophagy impairment in cholangiocarcinoma showing that autophagy induction, via rapamycin, as well as caspase inhibition, via Q-VD-OPh, are able to reduce proliferation marker PCNA level, colony size and protein content of cultured cholangiocarcinoma cells. The increased protein expression of p62, c-FLIP, caspase-10 observed in vitro in cholangiocarcinoma cells was paralleled by significant increase at gene expression levels in vivo; in fact, significant increase of transcript levels of p62, c-FLIP and caspase-10 was observed in 34 biopsies from human cholangiocarcinoma patients compared to 9 biopsies from 9 healthy controls, as reported in the GEPIA2 public database. The significant increase of p62 level in cholangiocarcinoma was found as a relatively uncommon finding in solid cancers, since it was also found in only 7 cancer types out of 31 cancer types investigated, including melanoma and hepatocarcinoma.In conclusion, we present data suggesting a molecular machinery controlling autophagy in cholangiocytes and autophagy impairment in cholangiocarcinoma.